(untitled) (Asian Journal of Social Science Studies, 2023)
The purpose of the research is to investigate the purchase behavior of Taiwanese consumers regarding multi-level marketing Health Food. The research focused on consumers who have purchased Health Food through multi-level marketing channels and aim to identify consumer behavior patterns. The study primarily focused on Taiwanese consumers and conducts an online questionnaire survey. A total of 322 responses were collected, and after excluding invalid questionnaires, the final sample size for the study was 305, with a utilization rate of 94.7%. Using IBM SPSS 25 for analysis, it was confirmed that among the demographic variables, only consumer age was significantly related to purchase behavior. Significant support was obtained for the association validation of the hypotheses, confirming the significant relationship between salesperson product information exposure and consumer purchase behavior of multi-level marketing Health Food, the significant relationship between consumer purchase behavior of multi-level marketing Health Food and consumer feedback, as well as the significant relationship between consumer feedback and Exposure of salesperson product information."